2021
DOI: 10.7759/cureus.17228
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Injuries in Soccer Players: A Narrative Review

Abstract: Soccer is one of the most popular sport, with many describing it as the "king of sports." In recent years, increased global participation in soccer has led to an inevitable increase in injury rates, especially in the lower extremities. Consequently, there is an increase in the epidemiology of soccer injuries, both in professionals and amateur athletes. The cause of an injury is multifactorial and depends on psychosocial, predisposing, intrinsic, and extrinsic factors. Also, contact with another player and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…The injury risk is multifactorial: it entangles a match between the intrinsic and extrinsic factors. On this road, we should be aware of biomechanical, anatomical, hormonal, physiological, psychological, social, and neuromuscular factors that involve and evolves the athlete ( 28 ). Therefore, it is urgent to reflect that intrinsic and extrinsic risk factors should be studied and monitored by the technical and medical teams.…”
Section: Discussionmentioning
confidence: 99%
“…The injury risk is multifactorial: it entangles a match between the intrinsic and extrinsic factors. On this road, we should be aware of biomechanical, anatomical, hormonal, physiological, psychological, social, and neuromuscular factors that involve and evolves the athlete ( 28 ). Therefore, it is urgent to reflect that intrinsic and extrinsic risk factors should be studied and monitored by the technical and medical teams.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal that in girls' basketball, the incidence of ankle injury stands at 2.08 per 1,000 athletic exposures while for boys, the incidence is slightly lower at 1.83 per 1,000 athletic exposures. Due to the demand of the ankle during repetitive cutting, running and posterior chain loading, soccer players face a common challenge [2]. The result of these high-speed lateral movements performed on the field or turf is that 66% of soccer injuries result in lateral ankle ligament injury with an additional 9% resulting in medial ankle ligament injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle injuries are often in high-demand sports, amounting to 10 to 55 % of all acute sports injuries. (6,7) Sports injuries are common in young athletes; young athletes frequently sustain sports-related injuries, and the likelihood is mostly due to earlier initiation of more vigorous practice and a higher degree of sports specialization compared to adult athletes. Several studies have sufficiently demonstrated that top athletes are more likely than athletes participating in recreational sports to experience trauma and overuse injuries and that these injuries also have an impact on their long-term health.…”
Section: Introductionmentioning
confidence: 99%